PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PADA MAHASISWA TERHADAP HASIL BELAJAR MATA KULIAH MEKANIKA ANALITIK - Salsabila, Puti Azka; Zihni, Wilda Eka Ibra; Setiaji, Bayu (Charm Sains: Jurnal Pendidikan Fisika, 2024)
The purpose of this study is to identify the factors that most influence the learning outcomes of analytical mechanics among students at Yogyakarta State University. This research uses a descriptive method with a questionnaire as the data collection instrument. The respondents consisted of 50 students from the Physics Education program at the FMIPA faculty. The results showed that the most dominant internal factor affecting the learning outcomes of analytical mechanics was health, with a percentage of 71%. This indicates that good physical health significantly influences students' ability to understand analytical mechanics. Additionally, the most dominant external factor was the influence of the lecturer, with a percentage of 40%. This reflects the important role of the lecturer in the learning process, including teaching methods, communication, and the motivation provided to students. In conclusion, both internal and external factors play significant roles in determining students' success in learning analytical mechanics.